Trust on thin ice - Maddox, Jake; Schenkel, Katie (Jake Maddox graphic novels., 2023)
Mina is a talented figure skater who is looking forward to trying the new challenge of pairs skating, but with shy boy Luke, she is beginning to have second thoughts, so they will have to overcome their trust issues to become a successful team.